Modelling habitat persistence and impacts of management on the habitats of an endangered butterfly. Issue 3 (1st February 2017) - Fabritius, Henna; McBride, Marissa
Abstract: In dynamic landscapes, effective species conservation requires an understanding of the spatial and temporal dynamics of species' habitats. In this study, vegetation data across differently aged sites, site management history data and expert elicitation are used to estimate (i) expected habitat patch lifetimes and (ii) the impacts of habitat management history on how habitat quality changes through time for an early‐successional habitat specialist, the endangered false heath fritillary butterfly ( Melitaea diamina ). Results demonstrate the accelerated temporal dynamics experienced by false heath fritillary habitats, with the quality of false heath fritillary habitats peaking 2–3 years after management, and a median‐sized habitat patch initially without tree cover predicted to become unsuitable 15 years after management due to overgrowth. As a co‐product of habitat management patterns, habitat succession and land use changes, non‐conserved false heath fritillary habitats had an expected lifetime of 13.1 years. This study demonstrates a method that can be used to estimate habitat network dynamics for an early‐successional habitat specialist economically in situations where the urgency of conservation challenges favours fast decision‐making.